2018
DOI: 10.1186/s12878-018-0110-7
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors of metabolic syndrome among adult Sudanese sickle cell anemia patients

Abstract: BackgroundSickle cell disease is a hereditary disorder characterized by haematological anaemia. Several studies assumed that adult sickle patients might develop metabolic syndrome features as hyperglycaemia, hypertension and dyslipidaemia. The aim of this study was to evaluate the metabolic syndrome risk factors among adult Sudanese with sickle cell anemia in the steady state.MethodsA prospective cross sectional study design was conducted among thirty adult patients with sickle cell anemia Hb SS (mean age 23 ±… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 17 publications
4
2
1
Order By: Relevance
“…Our results differ from some recent studies, in which fasting insulin 5 , fasting insulin and HOMA2‐IR 6 , or fasting glucose 7 were lower in SCA patients than controls. In the first study, however, β‐cell function negatively correlated with ferritin, and patients in the latter two studies were younger than the current cohort.…”
Section: Discussioncontrasting
confidence: 99%
“…Our results differ from some recent studies, in which fasting insulin 5 , fasting insulin and HOMA2‐IR 6 , or fasting glucose 7 were lower in SCA patients than controls. In the first study, however, β‐cell function negatively correlated with ferritin, and patients in the latter two studies were younger than the current cohort.…”
Section: Discussioncontrasting
confidence: 99%
“…In SCA high uric acid level may result from increased haemolysis and rapid turnover of the RBCs and decreased uric acid clearance by the kidneys (29). No significant difference regarding UA between sickle and control group (Table 3), this finding is similar to former study among Sudanese population (24). In this study hyperuricemia is reported only in 6.3% of SCA group; this likely due to the compensation of the high GFR (high UA clearance) among those young group; as age increases, GFR decreases and they may develop higher rates of hyperuricemia (30).…”
Section: Discussionsupporting
confidence: 84%
“…Significant reduction in diastolic Blood Pressure (BP) was noted (p value 0.02) in SCA group compared to the control group. Other studies also showed similar observations (15,23,24). This may be due to loss of sodium and water related to medullary tonicity defects (25).…”
Section: Discussionsupporting
confidence: 66%
“…From that point of view, the present results (elevated RER and %CHOox) suggest that glucose uptake and its subsequent utilization by the skeletal muscle are not dampened in patients with SCD. This latter inference is in accordance with the lower fasting blood glucose observed by Babiker et al 37 . Further studies would be necessary to characterize the relationship between this elevated glucose utilization and risk of metabolic syndrome in SCD; however, the prevalence of metabolic syndrome in sickle cell anemia patients has been reported to be approximately half of that in African-American counterparts 38 .…”
Section: Endurance Training Improves Metabolic Flexibilitysupporting
confidence: 92%